Novel mutations and defective protein kinase C activation of T-lymphocytes in ataxia telangiectasia - García-Pérez, M A (Blackwell Science Inc, 2001)
Three ataxia telangiectasia (AT) patients have been characterized immunologically and molecularly. Patient 1 presents two nondescribed splicing mutations which affect exons 15 and 21 of the ATM gene. The maternal defect consists of a G > A transition in the first nucleotide of the intron 21 donor splicing site which results in a complete deletion of exon 21. The paternal mutation consists of an A > C transversion in the intron 14 acceptor splicing site which produces a partial skipping of exon 15. Two abnormal alternative transcripts were found, respectively, 17 and 41 nucleotides shorter. Patient 2 presents a homozygous genomic deletion of 28 nucleotides in the last exon of the gene. This deletion changes the normal reading frame after residue 3003 of the protein and introduces a premature stop codon at residue 3008 that could originate a truncated ATM protein. Patient 3, a compound heterozygote, presents a defect which consists of a G > A transition in the first nucleotide of intron 62 donor splicing site which results in a complete deletion of exon 62. The results obtained during a three year period in the proliferation assays show an impaired PMA (phorbol myristate acetate) activation in specific T lymphocyte activation pathways (CD69, CD26, CD28, CD3, PHA, PWM and Con A mediated) but not in others (CD2, ionomycin, and Ig surface receptor). The possible link among specific ATM mutations and abnormal immune responses is unknown.